Listeria monocytogenes: survival and adaptation in the gastrointestinal tract - Gahan, Cormac G.; Hill, Colin (Frontiers in Cellular and Infection Microbiology, 2014)
The foodborne pathogen Listeria monocytogenes has the capacity to survive and grow in a diverse range of natural environments. The transition from a food environment to the gastrointestinal tract begins a process of adaptation that may culminate in invasive systemic disease. Here we describe recent advances in our understanding of how L. monocytogenes adapts to the gastrointestinal environment prior to initiating systemic infection. We will discuss mechanisms used by the pathogen to survive encounters with acidic environments (which include the glutamate decarboxylase and arginine deiminase systems), and those which enable the organism to cope with bile acids (including bile salt hydrolase) and competition with the resident microbiota. An increased understanding of how the pathogen survives in this environment is likely to inform the future design of novel prophylactic approaches that exploit specific pharmabiotics; including probiotics, prebiotics, or phages.